(untitled) (Faridpur Medical College Journal, 2013)
Wound management is a major concern in open fracture cases. Negative Pressure Wound Therapy (NPWT) is an advanced method for managing open wounds. It is a topical treatment using sub-atmospheric pressure to increase blood flow, remove bacteria and increase growth of granulation tissue in the wound. The study was performed to evaluate the results of NPWT in patients with open fracture in lower extremity. Using Aquarium pump as an NPWT device, 16 patients were prospectly treated for open fractures in their inferior extremity. Mean patients’ age range was 21 to 60 yrs. The patients under study either had suffered from trauma, fall or had post operative wound infection. Many of them had wounds with underlying tendon or bone exposure. Necrotic tissues were debrided before applying NPWT. Dressings were changed every 3rd or 4th day and treatments were continued for 07 to 28 days. Exposed tendons and bones were successfully covered with healthy granulation tissue in all cases, depth of the wounds reduced as well as surface areas. In 12 cases coverage of granulation tissue were achieved and further managed by skin grafting, 4 cases with wound infections were closed with secondary suture. No significant complications were noted regarding the treatment. NPWT was found to facilitate the rapid formation of healthy granulation tissue on open wounds in lower extremity and thus to shorten healing time and minimize secondary soft tissue defect coverage procedures. DOI: http://dx.doi.org/10.3329/fmcj.v7i2.13500 Faridpur Med. Coll. J. 2012;7(2):63-66